Exchange rate exposure of Hungarian enterprises - Results of a survey - Katalin Bodnár (Magyar Nemzeti Bank, 2009)
In this paper, I examine the exchange rate exposure of Hungarian enterprises from a financial stability perspective. In connection with the recent growth in FX loans to enterprises, the central bank assesses the vulnerability of the banks' loan portfolio to changes in the exchange rate. To collect company-level data, two surveys were carried out on exchange rate exposure and exchange rate risk management practices. The first survey carried out in 2005 showed that the majority of small and medium-sized enterprises are exposed to exchange rate depreciation, but that exchange rate risk management techniques are almost unknown to them. In the 2007 survey, which is summarized here, large enterprises were also examined, as well as motives for borrowing in foreign currency and the lack of FX risk management tools. Based on the results, the main motive for raising FX debt is lower interest rates, while at large enterprises natural hedging also appears as a factor. The main reason for ignoring FX risks is that FX risk management tools are thought to be expensive, complicated or ineffective. The majority of enterprises think there are no suitable tools to manage FX risks or they expect external solutions, such as the introduction of the euro to decrease their risks. Based on calculations on aggregated balance sheet data, exchange rate depreciations would improve the profitability of the corporate sector as well as its capability to repay the debts. However, micro-level calculations suggest that exchange rate depreciations increase the ratio of loss-making enterprises to a larger degree than exchange rate appreciations. These calcuations do not take competitiveness and other long-term effects of exchange rate changes into consideration, thus, the results have to be treated with caution.
Keywords: C25; C42; F31; G21; G32; 330; exchange rate exposure; FX borrowing; FX risk management; survey; probit; Kredit; Wechselkurs; Währungsrisiko; Währungsmanagement; Ungarn